Structural, Photocatalytic, and Antibacterial Evaluation of Cu-Doped ZnMn2O4 Nanoparticles - Soualmi, S.; Henni, M.; Djahnit, L.; Bouzegaou, M. (Eurasian Journal of Chemistry, 2025)
In this study, the impact of doping ZnMn2O4 spinel nanoparticles with different proportions of copper (Cu) was investigated for the first time. The nanomaterials were synthesized via sol-gel method and characterized structurally, optically, and morphologically. X-ray diffraction (XRD) confirmed the formation of a pure tetragonal spinel phase, with no secondary phases detected. Successful incorporation of Cu²⁺ ions into the ZnMn2O4 lattice was confirmed by shifts in peak positions and intensities. FTIR analysis revealed distinct Zn–O and Mn–O vibrations, confirming the structural integrity of the spinel. The optical band gap, estimated via Tauc plots, decreased from 2.61 eV for undoped ZnMn2O4 to 1.58 eV for 3 % Cu-doped samples, indicating improved light absorption properties. SEM analysis showed that Cu doping induced increased porosity and particle agglomeration. Photocatalytic activity was evaluated through the degradation of Methylene Blue under visible light; notably, the sample with 1 % Cu achieved an efficiency of 87.7 %. Furthermore, the doped nanoparticles exhibited strong antibacterial activity against both Gram-positive and Gram-negative bacteria, with pronounced inhibition observed against E. coli. These findings highlight the multifunctionality of Cu-doped ZnMn2O4 for environmental and biomedical applications.
Keywords: spinel; synthesis; nanomaterials; photocatalysis; doping; antibacterial; sol-gel; copper